SEKSISME DALAM BAHASA PRANCIS: KONSTRUKSI SOSIO-HISTORIS DAN POLITIS - Wening Udasmoro; Wiwid Nurwidyohening (Humaniora, 2006)
This paper aims at exploring the use of sexism in French language, which occurs frequently since the French Revolution in 1789. This sexism is historically and politically constructed by the society and espoused by different social actors, such as philosophers, politicians, religious leaders and others. The various forms of this sexism range from the level of syntax to semantics and place women in different categories. The overall analysis reveals that the women’s representations are underestimated, stigmatized and considered inferior vis à vis men’s representations.